Facile preparation of tissue engineering scaffolds with pore size gradients using the muesli effect and their application to cell spheroid encapsulation. Issue 6 (12th February 2020) - Forget, Aurelien; Rojas, Darling; Waibel, Michaela; Pencko, Daniella; Gunenthiran, Satyathiran; Ninan, Neethu; Loudovaris, Thomas; Drogemuller, Chris; Coates, Patrick T.; Voelcker, Nicolas H.; Blencowe, Anton
Abstract: Porous biodegradable scaffolds have many applications in bioengineering, ranging from cell culture and transplantation, to support structures, to induce blood vessel and tissue formation in vivo. While numerous strategies have been developed for the manufacture of porous scaffolds, it remains challenging to control the spatial organization of the pores. In this study, we introduce the use of the granular convection effect, also known as the muesli or brazil nut effect, to rapidly engineer particulate templates with a vertical size gradient. These templates can then be used to prepare scaffolds with pore size gradients. To demonstrate this approach, we prepared templates with particle size gradients, which were then infused with a prepolymer solution consisting of the pentaerythritol ethoxylate (polyol), sebacoyl chloride (acid chloride), and poly(caprolactone). Following curing, the template was dissolved to yield biodegradable polyester‐ether scaffolds with pore size gradients that could be tuned depending on the size range of the particulates used. The application of these scaffolds was demonstrated using pancreatic islets, which were loaded via centrifugation and retained within the scaffold's pores without a decrease in viability. The proposed strategy provides a facile approach to prepare templates with spatially organized pores that could potentially be used for cell transplantation, or guided tissue formation. Abstract :